Management of Invasive Mosquitoes Through Molecular Surveillance - Chong, Yee Ling; Mac, Pierce; Shaolin, Han; Lucy de, Lataillade; Yunshi, Liao; Elliott, Miot; Freddy Yeo, Kuok San; Benoit, Guénard; Tommy Lam, Tsan Yuk (World Scientific Publishing Europe Ltd., 2024)
In environmental and public health management, a number of mosquito species are considered pests and vectors of diseases. They are responsible for transmitting pathogens such as plasmodium and flaviviruses, causing the endemic circulation of those diseases in some countries. Notably, many of these mosquito vectors are exotic species which have undergone geographic expansion over the past centuries, leading to the dissemination of diseases outside of their native range. The spread and establishment of exotic mosquitoes and their associated mosquito-borne diseases (MBDs) are critical due to their public health implications and socio-economic costs. These have been facilitated by trade and globalisation, urbanisation, and climate change. Many countries and regions are vigilant about invasive mosquitoes and include them on the watchlist of their pest surveillance and control programmes. While conventional methods of species identification under microscopes are dominant approaches in mosquito surveillance, recent molecular techniques have been under active development and application in the field. This chapter summarises the state-of-the-art molecular methods, aiming to explain their strengths and limitations in providing timely and informative detection of mosquito invasion events and associated pathogens, which can guide subsequent control measures to hopefully eliminate exotic populations before they become established in new places.